RSM for Accelerated Biofilm Formation That Facilitates Bioremediation and Characterization of Biofilm (Global Journal of Science Frontier Research, 2012)
Pseudomonas stutzeuri a sewage isolate has been reported to produce extracellular polymeric substances(EPS) invitro and forms high quality biofilm in natural environment .An attempt is made to increase the extracellular polymeric substances and its Biofilm forming ability of the isolate using Design Expert-8 a statistical software .Various factors like concentration of carbon source, Nitrogen source , pH, Temperature are known to influence the process of EPS synthesis. FTIR reports strongly infer the presence of anionic glycoprotein polymer with stretching-NH vibrations around 3100 -3500nm and -CH vibration around 1637.99 indicating the presence of aldehyde group. HPLC further ensured the presence of glucose ,galactose ,rhamnose and verbacose at a concentration of 30%,22%,26%,25%and 5% respectively. Phenol sulphuric acid assay and Barfoards assay showed the presence of 60% and 30% of carbohydrate and protein components respectively. The polymer showed metal binding ability of 26% and 42% of lead and copper respectively complimented by its anionic nature. Extracted EPS showed noticeable emulsifying effect on diesel, engine oil, petrol and grease that can route this to successful tool for bioremediation.
Keywords: Extracellular polymeric substances; RSM; Biofilms; Anionic polymer